Ganho genético e seleção em gerações iniciais e em linhagens de trigo por meio de modelos mistos - Woyann, Leomar Guilherme (2018)
Wheat crop has great economic importance in Brazil, producing annually about 6 million tons. However, this production is only sufficient to meet ~ 50% of demand. This condition makes Brazil one of the largest importers of this cereal worldwide. The genetic improvement of this crop has great importance in the attempt of increasing production, productivity and quality of wheat produced in Brazil. Furthermore, increasing the efficiency of breeding programs is essential to reduce costs and the time required to release new cultivars. In this sense, solutions are necessary for the correct evaluation in steps where limited seeds are available or where the number of lines to be evaluated is very hight. Thus, the objectives of this work were: 1) to evaluate the genetic gain of wheat crop in Brazil in the last 30 years; 2) to use additive-dominant models, in generations F2 and F3, to identify the best parents for agronomic traits, i.e., grain yield, hectoliter mass, thousand grain mass, plant height, among others; and 3) to evaluate homozygous lines in designs without repetitions in multi-environment trials. For all analyses, mixed models were used. Genetic gain was evaluated using 126 Brazilian wheat cultivars released 1984 and 2014. Cultivars were evaluated in 187 trials, conducted in 25 locations, distributed in the Southern Region of Brazil, between 2002 and 2014. Environment effects was responsible for more than 70% of the total variance and genotypes presented similar behavior in the evaluated environments. Genetic gain was of 33.9 kg ha-1 year-1, which represents 1.28% year-1. Moreover, results indicated absence of stagnation in the genetic gain in Brazil. Analysis of F2 and F3 generations with additive-dominant models show cultivars and lines with high additive effects, which are the main effects when the objective is to release homozygous cultivars. For grain yield, cultivars TBIO Seleto, Mirante, TBIO Mestre, Sinuelo and Ametista and lines UTFT 0932, UTFT 0908 and UTFT 0944 presented the highest additive effects. In the analysis of adaptability, stability and productivity, lines UTFT 1110, UTFT 1608, UTFT 1620, UTFT 1025 and UTFT 1691 would be selected in each of the evaluated environments. However, lines UTFT 1634 and UTFT 1405 were among the selected lineages in the set of locations but could have been eliminated if the trial had been conducted in a design with replications in a single location.